2014
DOI: 10.1111/jocs.12419
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Transapical Cardioscopic Surgery in a Pig Model

Abstract: The proposed transapical cardioscopic platform is feasible for major intra-cardiac procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The quantity of Collagen I, III and IV are all signi cantly reduced in human aneurysms compared to non-aneurysmal acute ruptured porcine samples. Reassuringly there is good reproducibility of quanti cation between porcine and human non-aneurysmal samples as shown in earlier studies (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) Limitations in this study includes histological analysis, whereby immunohistochemistry techniques are limited by the ability of the tissue to take up by the antibodies in question which result in more di cult specimens to analyse and quantify. In addition, pathological analysis and quanti cation are limited by the investigator and varies considerably with each analysis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The quantity of Collagen I, III and IV are all signi cantly reduced in human aneurysms compared to non-aneurysmal acute ruptured porcine samples. Reassuringly there is good reproducibility of quanti cation between porcine and human non-aneurysmal samples as shown in earlier studies (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) Limitations in this study includes histological analysis, whereby immunohistochemistry techniques are limited by the ability of the tissue to take up by the antibodies in question which result in more di cult specimens to analyse and quantify. In addition, pathological analysis and quanti cation are limited by the investigator and varies considerably with each analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Using a physiological model, results could identify patterns in radiological, pathological, and histological changes that affect the aorta under stress. Although no studies apart from Surman et al (1) have reported on the maximal pressures obtained in the porcine aortic root and ascending aorta, many studies have showed that a porcine model is effective in the application of cardiopulmonary bypass and replicating models applicable to human subjects in cardiothoracic surgery (4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of Collagen I, III and IV are all significantly reduced in human aneurysms compared to non-aneurysmal acute ruptured porcine samples. Reassuringly there is good reproducibility of quantification between porcine and human nonaneurysmal samples as shown in earlier studies [4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 87%
“…Using a physiological model, results could identify patterns in radiological, pathological, and histological changes that affect the aorta under stress. Although no studies apart from Surman et al [1] have reported on the maximal pressures obtained in the porcine aortic root and ascending aorta, many studies have showed that a porcine model is effective in the application of cardiopulmonary bypass and replicating models applicable to human subjects in cardiothoracic surgery [4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation